APLIKASI KONSEP HILAH DALAM PENGEMBANGAN PRODUK PERBANKAN SYARIAH - H. Muhammad Taufiki (Jurnal Dialog, 2017)
The development of syariah compliant banking products can not be separated from the use of classical Islamic methods. One of them is the method called hilah which is literally meant to make something lawful according to Islam. In its development, this concept exists and becomes one of the methods used in the making of fatwa of the DSN-MUI. This article describes the use of hilah in the implementation of syariah compliant banking products such as syariah charge card.